2018
DOI: 10.3389/fendo.2018.00747
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Amide Proton Transfer Imaging and ZOOM Diffusion-Weighted Imaging in Differentiating Benign and Malignant Thyroid Micronodules

Abstract: Background: Pre-operative non-invasive differentiation of benign and malignant thyroid nodules is difficult for doctors. This study aims to determine whether amide proton transfer (APT) imaging and zonally oblique multi-slice (ZOOM) diffusion-weighted imaging (DWI) can provide increased accuracy in differentiating benign and malignant thyroid nodules.Methods: This retrospective study was approved by the institutional review board and included 60 thyroid nodules in 50 patients. All of the nodules were classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Consequently, the intra- and inter-observer agreements with RT-DWI and NT-DWI were lower than with Z-DWI. Previous studies have shown that Z-DWI has obvious advantages in cervical cancer 28 , thyroid micronodules 29 , cervical spinal cord 30 , etc. It enables clearer identification of lesions and reduction of image artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the intra- and inter-observer agreements with RT-DWI and NT-DWI were lower than with Z-DWI. Previous studies have shown that Z-DWI has obvious advantages in cervical cancer 28 , thyroid micronodules 29 , cervical spinal cord 30 , etc. It enables clearer identification of lesions and reduction of image artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have proven that the use of functional MRI imaging sequences, such as amide proton transfer imaging, intravoxel incoherent motion and diffusion kurtosis imaging (DKI) have certain significance in the differential diagnosis of benign and malignant thyroid lesions (Liu et al, 2018; Shi et al, 2017; Tan et al, 2019). At present, NG is a common benign thyroid disease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is less sensitive to the inhomogeneity of the magnetic field. And many previous studies have proven that as a novel imaging technology, rFOV‐DWI has great diagnostic value in differentiating benign and malignant thyroid lesions (Hao et al, 2016; Liu et al, 2018). As a reverse recovery sequence with multiple TI values, T1 mapping can accurately and quantitatively determine the T1 value of lesions, such as internal tissue information including water content and fibrosis (Nacif et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported on a study about patients with thyroid tumors that showed the feasibility of performing APTw imaging in the neck. The results showed that the APTw values of malignant nodules of the thyroid are lower than that of benign nodules, which is different from other tumors (16). However, thyroid tumors are prone to cystic change (17), which have a significant influence on the measurement of APTw values.…”
Section: Introductionmentioning
confidence: 89%